KEANEKARAGAMAN DAN DOMINANSI SPESIES BELALANG (ORTHOPTERA) DI HUTAN RAYA BALAS KLUMPRIK SURABAYA SEBAGAI SUMBER BAHAN AJAR BIOLOGI - Yestyas Ramadiah Hanum; Bintang Vania Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Grasshoppers are often considered agricultural pests, although they play important ecological roles as decomposers, pollinators, and consumers in food webs. This study aimed to identify and analyze the diversity and dominance of grasshopper species in Balas Klumprik Urban Forest, Surabaya. The research was conducted from February to March 2024 using purposive sampling at three observation stations. Four families comprising six species were identified: Atractomorpha crenulata, Phlaeoba fumosa, Oedalus infernalis, Oxya japonica, Conocephalus longipennis, and Tetrix undulata. The Shannon–Wiener diversity index was 1.11 (moderate), while the dominance index was 0.4232 (low), indicating suitable habitat conditions for grasshopper diversity. These findings highlight the importance of conserving insect biodiversity in urban forests and support Sustainable Development Goal (SDG) 15 on Life on Land. The results also have potential as a contextual learning resource for senior high school Biology, particularly on biodiversity, to enhance students' understanding and environmental awareness.